Evaluasi Usabilitas Aplikasi DLU Ferry Pasca-Optimalisasi Menggunakan System Usability Scale (SUS) dan A/B Testing: Studi Kasus dengan Pendekatan Design Thinking - Fablo Aimar; Anugrah Nur Rahmanto; Usman Nurhasan (TeIKa, 2025)
The DLU Ferry application has not fully met user expectations in terms of ease of understanding information on schedules, fares, and supporting features, and often experiences data synchronization issues that can undermine user confidence. This study aims to optimize the user interface of the DLU Ferry application to meet user needs for clear, accessible, and real-time information. The Design Thinking approach (Empathize, Define, Ideate, Prototyping, Testing) was chosen because it prioritizes user-centricity, facilitates a deep understanding of user needs and challenges, and enables the creation of sustainable and iterative solutions. Quantitative testing was conducted using the System Usability Scale (SUS) and A/B Testing. The final iteration of the SUS testing yielded an average score of 86, indicating the “Excellent” or “Best Imaginable” category in terms of usability, proving the success of the optimization efforts. However, there are areas for continuous improvement based on respondent feedback, including enhancing application performance and stability, refining the user interface, adding features, improving information quality and accessibility, and strengthening customer service and integration.